Market Power And Efficiency Of Commercial Banks In Indonesia - Wita Juwita Ermawati, Eny Susilowati, Budi Purwanto, (Jurnal Manajemen, 2019)
In order to encourage credit growth that experienced sluggishness from 2012 to 2016, Bank Indonesia sought to increase lending by lowering the benchmark interest rate so that it could be followed by a decline in lending rates by banks in Indonesia. But this is thought to cause competition to become a low oligopoly and decrease efficiency. This study aims to determine the factors that affect the amount of credits paid, estimating the market power and efficiency of commercial banks in Indonesia for the 2012-2016 period. Efficiency method used is Data Envelopment Analysis, while to estimate market power using two stage least square. The results of the demand equation show GDP and WCCR_GDP have no significant effect while the rest variables have significant effect. From the two equations using Bresnahan-Lau’s model, market power is 0.231. Efficiency measurement obtained a good efficiency scale even reaching 100% in 2013, 2015 and 2016.